Investigation of Sewage Flows in Universiti Malaysia PAHANG’s Sewerage System - Ngien, S. K.; Norasman, Othman; Nadiatul Adilah, Ahmad Abdul Ghani (2015)
Sewerage systems have long been one of the most critical infrastructure to any development project. The study presented here is part of a research that aim to evaluate the flow characteristics in sewerage systems. Sewage flow data was collected from a sewerage catchment within Universiti Malaysia PAHANG using an area-velocity flowmeter. The data obtained were extracted using a software associated to the flowmeter and analyzed for both dry and wet periods. The results show that the peak or maximum flow for the wet period with a rainfall intensity of 2.5 mm was twice as high for the dry period. The design criterion value back-calculated for the wet period was also twice the value for the design criterion value back-calculated for the dry period. This demonstrates that rainfall has an important effect on flows in sewerage system in that it increases the flow significantly. The k value back-calculated for both dry and wet periods were lower than the criterion recommended in Malaysian Standard MS1228:1991, suggesting that the current peak flow factor equation applied by the industry is over-adequate for sewerage catchments servicing the same population equivalent as this study.